KEDIRI TOURISM DEVELOPMENT STRATEGY MANAGEMENT USING THE BLUE SEA STRATEGY APPROACH - Dita Riyanto Putro; Ana Komari; Lolyka Dewi Indrasari (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Competition in the tourism industry in Indonesia is currently very tight, with each region competing to highlight its uniqueness. With this very tight competition, Kediri Regency is trying to get out of the competition (red ocean) by creating innovations through the concept of the Blue Ocean Strategy. Blue Ocean Strategy is a term in the science of strategic management that refers to a strategy to create new markets that have not been filled with intense competition. Blue Ocean Strategy is a strategy to conquer competitors by offering innovative product features, which have so far escaped the attention of competitors. This study uses a qualitative methodology using the results of observations, interviews, and document reviews. While this type of research is categorized as descriptive research. This descriptive qualitative approach facilitates in-depth exploration of strategic management in tourism development using the Blue Ocean Strategy approach at the Kediri Regency Tourism and Culture Office. The results of the study show that tourism development with the Blue Ocean Strategy approach has not been implemented formally and officially, but the elements in the Blue Ocean Strategy approach have been adopted by the Tourism and Culture Office of the Kediri Regency in developing tourism using the value of innovation.